Beliefs about Violence: A Brazilian Study from the Piagetian point of reference - Alves Monteiro, Tamires; Giachetto Saravali, Eliane [UNESP] (Univ Rosario, 2015)
The paper presents part of a study substantiated on the Piagetian theory and investigations about the construction of social knowledge, and the study goal is to examine the ideas of children and adolescents about violence. The study was conducted with 40 subjects aged between 6 and 15 years. In this paper we present data obtained from one of the methodological tools used in the research-a drawing of a person who is suffering violence and another one that does not suffer. Results indicate that the drawings of most subjects fail to portray the phenomenon of violence in all its complexity. There is a tendency to associate it with only the most visible and concrete aspects of the situations or conflicts portrayed, focusing on an elementary level of understanding of social reality.
Keywords: violence; social knowledge; Piagetian theory; drawing